Development of an ankle torque measurement device for measuring ankle torque during walking - Tanino, Genichi (J Phys Ther Sci, 2015)
[Purpose] To develop a device for measuring the torque of an ankle joint during walking in order to quantify the characteristics of spasticity of the ankle and to verify the functionality of the device by testing it on the gait of an able-bodied individual and an equinovarus patient. [Subjects and Methods] An adjustable posterior strut (APS) ankle-foot orthosis (AFO) was used in which two torque sensors were mounted on the aluminum strut for measuring the anterior-posterior (AP) and medial-lateral (ML) directions. Two switches were also mounted at the heel and toe in order to detect the gait phase. An able-bodied individual and a left hemiplegic patient with equinovarus participated. They wore the device and walked on a treadmill to investigate the device’s functionality. [Results] Linear relationships between the torques and the corresponding output of the torque sensors were observed. Upon the analyses of gait of an able-body subject and a hemiplegic patient, we observed toque matrices in both AP and ML directions during the gait of the both subjects. [Conclusion] We developed a device capable of measuring the torque in the AP and ML directions of ankle joints during gait.